Meta-Analysis of Constructivist Learning Models in Improving Student Learning Outcomes - Syahid, Akhmad; Subaedah, Subaedah; Nurbaeti, Nurbaeti; Arsyam, Muhammad (Pascasarjana Universitas KH. Abdul Chalim, 2023)
This article aims to revisit and find out to what extent the constructivist learning model is able to improve student learning outcomes. Learner learning outcomes are one indicator of the success of education in the cognitive domain, of course, supported by the learning model. The focus of research on the implementation of constructivist learning models can improve student learning outcomes in elementary schools. The research method and approach used is a descriptive qualitative meta-analysis by collecting several research results with document studies and research data derived from journals related to the implementation of constructivist learning models. The data collection technique used is non-test by searching E-journals via Google Scholar or Google Scholar as well as documentation studies conducted in the library. Searches obtained several articles and 9 theses, 1 thesis, and 1 dissertation related to constructivist learning models. The results indicated that the constructivist learning model was able to improve student learning outcomes with the lowest percentage of 21% to the highest of 53% with an average of 32.35%. So it is concluded that the implementation of constructivist learning models in the learning process based on E-journal searches through Google Scholar, Google Scholar, and documentation studies is effective in improving student learning outcomes.